Defending the "people of truth" in the early Islamic period : the Christian apologies of Abū Rā̕̕iṭah - Keating, Sandra Toenies. (The History of Christian-Muslim Relations, 2006)
The apologetical writings of the Jacobite Christian, Abū Rā'iṭah al-Takrītī († c. 835) have remained relatively unknown in Western scholarship. Yet his engagement with Muslim questions about Christianity provides a significant insight into the theological debate between the two communities in the early ʿAbbāsid period. Abū Rā'iṭah's treatises take up many of the topics that become standard for Christian-Muslim apologetics: proofs of the true religion, the Trinity, the Incarnation, and Christian practices. In each case, he provides his reader with complex arguments in defense of Christian doctrines that can be used to convince both Muslims and wavering Christians of the truth of Christianity. This new Arabic edition and English translation seeks to contextualize Abū Rā'iṭah's important writings and to make the original texts available to modern scholars interested in all aspects of the early development of Muslim-Christian relations.